2012
DOI: 10.4049/jimmunol.1201022
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- and Ligand-Specific Sensing of Gram-Negative Infection in Drosophila by PGRP-LC Isoforms and PGRP-LE

Abstract: The Drosophila antimicrobial response is one of the best characterized systems of pattern recognition receptor-mediated defense in metazoans. Drosophila senses Gram-negative bacteria via two peptidoglycan recognition proteins (PGRPs), membrane-bound PGRP-LC and secreted/cytosolic PGRP-LE, which relay diaminopimelic acid (DAP)-type peptidoglycan sensing to the Imd signaling pathway. In the case of PGRP-LC, differential splicing of PGRP domain-encoding exons to a common intracellular domain-encoding exon generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 50 publications
5
126
0
Order By: Relevance
“…Flies feeding on these fruits may ingest the corresponding peptidases, where they immediately come into contact with the intestinal epithelium. Presumably to counteract the unwanted activation of this arm of the immune system by ingested peptidases, the major PRR PGRP-LC is not present or is present at only very low levels in the midgut of the fly (36). Our own observations support this finding.…”
Section: Discussionsupporting
confidence: 80%
“…Flies feeding on these fruits may ingest the corresponding peptidases, where they immediately come into contact with the intestinal epithelium. Presumably to counteract the unwanted activation of this arm of the immune system by ingested peptidases, the major PRR PGRP-LC is not present or is present at only very low levels in the midgut of the fly (36). Our own observations support this finding.…”
Section: Discussionsupporting
confidence: 80%
“…Ectopic expression of PGRP-LE in the fat body is sufficient to activate AMP expression, in a cell-autonomous fashion, in the absence of infection. It also was shown that cytoplasmic PGRP-LE can activate the Imd pathway, independently of PGRP-LC, by interacting with Imd (40)(41)(42)(43). PGRP-LE is the only intracellular pathogen receptor identified in Drosophila.…”
mentioning
confidence: 99%
“…PGRP-LC mutant flies are still responsive toward TCT. This is due to PGRP-LE, which is found in two forms (40,41). The short form is secreted and binds PGN in the hemolymph (42) and is thought to assist Imd signaling by presenting PGN to PGRP-LC, although the export mechanism of PGRP-LE has not been characterized.…”
mentioning
confidence: 99%
“…The Imd pathway, which is similar to the mammalian TNF and TIR-domaindependent TLR pathway, recognizes diaminopimelic acid (DAP)-type peptidoglycan found in Gram-negative bacteria and Gram-positive Bacilli, as well as peptidoglycan monomers (also referred to as TCT, for tracheal cytotoxin) of Gram-negative bacteria. The surface-bound receptor PGRP-LC and cytosolic receptor PGRP-LE are the main Imd receptors in the fat body and, as described in more detail below, are also found in the gut [29][30][31][32][33].…”
Section: Drosophila Detection Of Microbes and Amp Productionmentioning
confidence: 99%
“…As in the systemic response, both the transmembrane receptor PGRP-LC and intracellular PGRP-LE recognize peptidoglycan in the gut and induce the Imd pathway cascade [31,32]. However, whereas both receptors are associated with fat body cells in the haemocoel, in the gut the activity of these receptors is regionalized, with PGRP-LC being localized to the fore-and hindgut, while PGRP-LE is restricted to the midgut [32]. AMPs are most highly expressed in the anterior midgut [67,89,90], where they are thought to reduce or eliminate potential pathogens ingested with the food.…”
Section: Amps and Gut Immune Responsesmentioning
confidence: 99%